Benzophenone-3 and benzophenone-8 exhibit obesogenic activity via peroxisome proliferator-activated receptor γ pathway. (September 2020) - Shin, Jeayoung C.; Lee, Eunyoung; An, Seungchan; Jin, Sun Hee; Ha, Jaehyoun; Choi, Won Jun; Noh, Minsoo
Abstract: Benzophenone-3 (BP-3) and benzopenone-8 (BP-8) are commonly used ultraviolet (UV) filter ingredients in diverse sunscreen products. Recently, the obesogenic activity of avobenzone, a long wave UV A filter, was elucidated in the adipogenesis model of human bone marrow mesenchymal stem cells (hBM-MSCs). In this study, the obesogenic potentials of BP-3 and BP-8 were investigated because of their chemical similarity to avobenzone. During the adipogenesis in hBM-MSCs, BP-3 and BP-8 (EC50, 25.05 and 43.20 μM, respectively) potently promoted adiponectin secretion than avobenzone (EC50, 72.69 μM). In target identification, both BP-3 and BP-8 directly bound to peroxisome proliferator-activated receptor γ (PPARγ), which was associated with the recruitment of steroid receptor coactivator-2 (SRC-2). BP-3 functioned as a PPARγ full agonist whereas BP-8 was a PPARγ partial agonist. In addition, BP-3 and BP-8 significantly increased the gene transcription of PPARα, PPARγ, and major lipid metabolism-associated enzymes in human epidermal keratinocytes, a major target site of UV filters in human skin. This study suggests that BP-3 and BP-8 are obesogenic environmental chemicals similar to phthalates, bisphenols, and organotins. Graphical abstract: Unlabelled Image Highlights: BP-3 and BP-8 promoted adiponectin secretion during adipogenesis in hBM-MSCs. Obesogenic effects of BP-3 and BP-8 were mediated by PPARγ signaling. BP-3 and BP-8 acted as full and partial PPARγ agonists, respectively. BP-3 and BP-8 are environmental obesogenic similar to other established toxins.